Il catalogo musicale pop e il cinema delle emozioni: il caso "Yuppi Du" (1975) (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
In the 1970s, film language faced a change towards a more intensified relationship with the viewer. In my contribution, I consider the case study of “Yuppi Du”, a rock opera authored by singer Adriano Celentano in 1975, one of the most conscious attempts in Italy to follow the new trends in musical film. On the basis of recent researches in the psychology of rhythm and musical timing, I delve into the emotional qualities of a narrative and stylistic formula which is structured not by the plot, but by a succession of songs comparable with a concept album, or a pop catalogue.
Keywords: Celentano; rock opera; film music; sound studies; rhythm